Assessment of Noise Pollution in the Ashuganj Fertilizer Industrial Area, Ashuganj (Bangladesh Journal of Scientific and Industrial Research, 2011)
Noise pollution in industries is now a serious environmental concern in Bangladesh. In this study sound levels are observed inside the Ashuganj Fertilizer Company Ltd (AFCL) Ashuganj. Continuous running of high speed turbo machinery, vibration of pipelines and structures, transmission of high pressure gas, sudden release of high pressure gas generate noise hazard inside the factory during the time of production. The sound level data was collected at seventeen different locations in the ammonia production plant, ten different locations in the urea production plant and ten different locations in the residential area of AFCL. In the ammonia plant, significantly high level of sound was observed (>90dB) from the process gas cooler, let-down station, boiler-feed water pump, synthesis-gas compressor, process air compressor, alternator and ammonia compressor areas. In the Urea plant, Prill tower (top), Prill tower (absorber vent) are the most noise vulnerable areas with sound level >90 dB. Residential area found less affected by noise pollution (43-53 dB) but in some areas like playground, main gate of the residential area sound level sometimes cross the standard sound level of residential area (50 dB). In the ammonia and urea plant, the sound levels are much higher than the standard sound level (75 dB) for the industrial area, which is considered a hazard of noise may induce hearing loss, annoyance and other adverse effects on the health of the workers of AFCL. Therefore, some remedial measures should be taken to reduce the sound level inside the factory. Key words: Noise pollution; Ashuganj Fertilizer Company Ltd (AFCL); Ammonia production plant; Urea production plant; Sound level; Health hazard. DOI: http://dx.doi.org/10.3329/bjsir.v46i2.8184 Bangladesh J. Sci. Ind. Res. 46(2), 183-190, 2011